THE CHARACTERISTICS OF WATER-IN-BIODIESEL EMULSIONS PRODUCED USING ULTRASONIC HOMOGENIZER - KAUR, EESHA (IRC, 2018)
Emulsions have always been considered as an alternative fuel for combustion in order to achieve better fuel economy and pollution reduction. While the method of mechanical homogenization is commonly used to produce water-in-biodiesel emulsions, the application of an ultrasonic homogenizer to produce emulsified fuels is still quite limited. The characteristics of the emulsion depend strongly on production method. This project aims to prepare and characterize water-in-biodiesel emulsion samples and subsequently, ascertaining the optimum water-in-biodiesel emulsion that meets the specification for a diesel engine. Characterization tests were carried out on 48 water-in-biodiesel samples produced using direct sonication, with water percentages of 9%, 11%, 13% and 15%, surfactant dosages of 5%, 7% and 9%, and HLB values of 6, 7, 8 and 9. The tests consisted of water droplet size, stability, density and viscosity.